A Rare Case of Puberty Onset Congenital Erythropoietic Porphyria with Ophthalmological Manifestations - Debjani, Mishra (Middle East Afr J Ophthalmol, 2016)
A 27-year-old male patient was presented with foreign body sensation in both the eyes for 2 years duration and blisters followed by scarring and pigmentation in the photo-exposed areas of the body over the previous 12 years. His urine was reddish colored for the previous year. On examination, there was scarring, hyper-pigmentation of photo-exposed parts of the body along with resorption of the distal phalanges of fingers in both hands except the smallest digit which had onycholysis. Ocular examination indicated scleral necrosis in the interpalpebral areas in both eyes and bilateral dry eye. Hematological examination indicated a picture suggestive of hemolytic anemia. Abdominal ultrasonography indicated an enlarged spleen. These clinical features are suggestive of puberty onset congenital erythropoietic porphyria with ophthalmological manifestations.